THESAURUS OF THE LEMMA ’TEACHER’ IN THE ACADEMIC DISCOURSE OF ONLINE LEARNING: A CORPUS-BASED STUDY - Denysova, Nataliia; Tsapro, Galyna (The Modern Higher Education Review, 2024)
The adoption of online learning has significantly transformed educational practices, sparking extensive debate about its effectiveness, challenges, potential. Central to these discussions are the roles of educators and students, innovative strategies for maintaining engagement, and the integration of technology to meet diverse learning needs. Teachers, as key figures in online education, play a crucial role in determining the success of these digital environments. This article examines the thesaurus of the lemma "teacher" within academic texts on online learning and compares it with dictionaries and the article’s literature overview to provide a comprehensive understanding of how the role of the teacher is framed. The thesaurus analysis reveals that words like "student" and "learner" reflect the student-centered nature of online education, while "instructor" is a more formal synonym. Words such as "parent," "participant," and "user" point to the broader ecosystem, including various stakeholders and digital platforms. Additionally, "course," "school," and "education" emphasize the structural aspects of learning, and "support" underscores the teacher’s role in providing guidance. This highlights the teacher’s evolving role as an educator, mentor, and collaborator in online education. The literature overview primarily focuses on the teacher’s responsibilities in managing classrooms, designing lessons, and assessing student performance, along with challenges like adapting to technology and maintaining student engagement. In contrast, the corpus offers a more comprehensive perspective, highlighting the interconnected roles of stakeholders, the importance of technological tools, and strategies for fostering engagement. While both perspectives recognize the teacher’s significance, the corpus provides a broader view of online learning, considering environmental factors, learner characteristics, and instructional models. By comparing these two perspectives, the study emphasizes how online education is shaped not only by teachers’ roles but also by the broader educational ecosystem, technological advancements, and learner engagement strategies.